The sentences imposed by the Huancavelica's criminal judges in the cases of medical malpractice in 2016 - Arzapalo Rodríguez, Amanda (2018)
In the course of time, the practice of medicine became detached from its primitive priestly character and has slowly transformed into an exercise performed exclusively by doctors. The objective of the present research was to know if Huancavelicanos criminal judges render effective sentences to deprivation of liberty to doctors in cases of medical malpractice in 2016. The methodology is of the type of Descriptive Legal Research, also called diagnostic research, which is used when the objective is to detail how they are and how they manifest phenomena, situations, contexts and events. The results were that the criminal judges of the High Court of Justice in Huancavelica, do not declare sentences term of imprisonment in the crimes of medical malpractice, opting for suspended sentences. It was determined that 60% of the cases have indicated that the penalty of disqualification should apply to doctors who are sentenced with term of imprisonment in the medical malpractice.